3D approach for the integration of new design methods applied to a middle-size company in the cosmetic sector. (20th February 2009) - Perrin-Bruneau, Flore; Millet, Dominique; Aoussat, Ameziane; Roatta, Isabelle
As a way to successfully change collective practices, the integration of new design methods is seldom mentioned in the literature. It is the contention of this article that in order to change collective practices, it is necessary to put into place a genuine integration strategy. We propose here an integration plan that consists of conceiving and applying three strategies: definition of the tool, demonstration of the method and diffusion of collective practices. The respective goals of these three strategies are to encourage individual appropriation, generate a valorisation of the method and harmonise collective practices for the whole organisation. This approach was tested on two integration projects of new design methods at Bourjois, a company in the cosmetic sector.